2011
DOI: 10.1074/mcp.m110.002964
|View full text |Cite
|
Sign up to set email alerts
|

Increased Protein Nitration in Mitochondrial Diseases: Evidence for Vessel Wall Involvement

Abstract: Mitochondrial diseases (MD) are heterogeneous disorders because of impairment of respiratory chain function leading to oxidative stress. We hypothesized that in MD the vascular endothelium may be affected by increased oxidative/ nitrative stress causing a reduction of nitric oxide availability. We therefore, investigated the pathobiology of vasculature in MD patients by assaying the presence of 3-nitrotyrosine in muscle biopsies followed by the proteomic identification of proteins which undergo tyrosine nitrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(49 citation statements)
references
References 42 publications
4
41
0
2
Order By: Relevance
“…Another study has demonstrated that sarcoplasmic NOS activity is reduced in cytochrome c oxidase (COX) deficient fibers of muscle biopsies obtained from patients with chronic progressive external ophthalmoplegia (CPEO), mitochondrial myopathy, and MELAS syndrome [2]. Flow-mediated vasodilation (FMD), which is a function of NO synthesized by endothelial cells in response to re-perfusion, was found to be impaired in patients with mitochondrial myopathy, MELAS, MERRF (myoclonic epilepsy with ragged red fibers), MIDD (maternally inherited diabetes and deafness), and CPEO, providing further evidence of NO deficiency in mitochondrial diseases [4,6].…”
Section: Nitric Oxide Deficiency In Mitochondrial Diseasesmentioning
confidence: 99%
See 2 more Smart Citations
“…Another study has demonstrated that sarcoplasmic NOS activity is reduced in cytochrome c oxidase (COX) deficient fibers of muscle biopsies obtained from patients with chronic progressive external ophthalmoplegia (CPEO), mitochondrial myopathy, and MELAS syndrome [2]. Flow-mediated vasodilation (FMD), which is a function of NO synthesized by endothelial cells in response to re-perfusion, was found to be impaired in patients with mitochondrial myopathy, MELAS, MERRF (myoclonic epilepsy with ragged red fibers), MIDD (maternally inherited diabetes and deafness), and CPEO, providing further evidence of NO deficiency in mitochondrial diseases [4,6].…”
Section: Nitric Oxide Deficiency In Mitochondrial Diseasesmentioning
confidence: 99%
“…Increased protein nitration has been reported to occur in endothelial cells of small blood vessels in muscle tissues from subjects with different mitochondrial diseases including mitochondrial myopathy, MELAS, MERRF, MIDD, and CPEO [6]. Based on these findings it was suggested that oxidative stress in mitochondrial diseases results in decreased NO availability by shunting NO into reactive nitrogen species formation [6]. Therefore, NO deficiency can result from post-production scavenging of NO by COX and/or the diversion of NO to reactive nitrogen species formation.…”
Section: Post-production No Scavengingmentioning
confidence: 99%
See 1 more Smart Citation
“…However, several hypotheses have been proposed; the most commonly accepted is an aberrant vascular tone caused by abnormalities in the vascular smooth muscle and endothelium. A study by Vattemi et al (Vattemi et al 2011) suggested that in MELAS patients, the vessel wall is a target of oxidative stress and that the degree of endothelial dysfunction is related to age and oxidative stress. First, regarding endothelial dysfunction, nitric oxide (NO) synthesis by endothelial nitric oxide synthase (eNOS) was decreased.…”
Section: Discussionmentioning
confidence: 99%
“…There is growing evidence that NO deficiency occurs in at least some MD and can play a major role in the pathogenesis of stroke-like episodes, myopathy, diabetes mellitus, and lactic acidosis [3,[5][6][7][8][9][10]. As such, NO measurements in patients with mitochondrial disease could be an important tool for understanding the pathogenesis and stages of the disease, assisting in the diagnosis, and monitoring response to treatment.…”
Section: Introductionmentioning
confidence: 99%